Novel gas‐based nanomedicines for cancer therapy. Issue 1 (31st January 2022) - Yao, Xianxian; Yang, Binru; Xu, Jian; He, Qianjun; Yang, Wuli
Abstract: Gas therapy, an emerging cancer treatment method of inflammation‐related diseases, has recently received substantial attention. The rapid advances in nanomedicine and nanotechnology have made gas precision treatment possible through tumor targeted delivery and controlled release of therapeutic agents. Single therapeutic is often inevitably accompanied with limited therapy efficacy. Gas therapy combined with other treatment methods can sensitize different therapy modes to augment cancer therapy. Understanding the mechanism through which gas enhances other therapeutic modalities will enable the design of reasonable strategies for clinical cancer therapy. In this review, we summarize novel gas‐based nanomedicines, focusing on gas‐based nanomedicine carriers, along with the release of gas molecules and the mechanisms of gas enhanced therapy. We describe the design of novel gas‐releasing nanoplatforms and the underlying synergistic mechanisms against cancer. Moreover, we describe the current challenges and outlook for future prospects in novel gas‐based nanomedicines for gas therapy in cancer. Abstract : In this review, novel gas‐based nanomedicines along with the release of gas molecules and the mechanisms of gas enhanced therapy are summarized. Gas therapy combined with other treatment methods can sensitize different therapy modes to augment cancer therapy and efforts should be made to understand the mechanisms and develop applications to accelerate the adoption of gas therapy in clinical settings.